Konstitutionen av den speciella pedagogiken i en barncentrerad förskola för alla: Att analysera politiska styrinstrument utifrån diskursteoretisk ram - Palla, Linda (Studier i Pædagogisk Filosofi, 2018)
This paper identifies and analyzes what constitutes special education in the revised Swedish preschool curriculum. The paper also contributes with an analytical mode of understanding political, as well as other, documents, in, for example, an educational system. The analytical strategy is mainly built upon discourse theory and discourse analysis, using the ideas of Ernesto Lacalu, Chantal Mouffe and Michel Foucault. The results show a fortified hegemonic discourse about a preschool for all children, where child-centred and inclusive approaches are dominant and where special education, to a large extent, is constituted by more management, stimulation and special support. The paper raises questions about the possible effects the hegemonic discourse may contribute to. Nyckelord: diskurs, diskursanalys, diskursteori, läroplan, specialpedagogik, inkludering, pedagogik, styrdokument, svensk förskola för alla barn, utbildning